Determination of Use of Alternative Medicine Methods in Patients With Ankylosing Spondylitis - Ozel, Filiz; Yetim, Burcu Cokmez; Yatarkalkmaz, Sevgi; Karabulut, Gonca (Ovid Technologies (Wolters Kluwer Health), 2020)
This study aimed to examine complementary and alternative medicine (CAM) use among patients with ankylosing spondylitis (AS) who had or who had not received treatment with biological agents; the study also aimed to determine the types of CAM methods used by these patients. This is a comparative and cross-sectional study. This research was conducted at a rheumatology outpatient clinic of a university hospital in Turkey. A total of 120 patients who had (n = 60) and had not (n = 60) received therapy with biological agents participated in this study. A patient identification form and a questionnaire prepared by the researchers were used to collate the study data. This study found that the most commonly used method among patients who did not receive biological therapy was thermal facilities, at a rate of 28.3%; and that the most commonly used method among patients who did receive biological therapy was the use of thermal facilities, at a rate of 25%. No significant difference was found between patients who had received and patients who had not received biological therapy in terms of age and disease duration. Information was provided by health professionals to the patients concerning frequently used CAM modalities.
Keywords: Complementary Therapies; rheumatology; Biological Factors; Cross-Sectional Studies; biological agents; Complementary; Surveys and Questionnaires; ankylosing spondylitis; Humans; Spondylitis, Ankylosing; patient; complementary and alternative medicine; 3. Good health